A = 1/2h(B + b) = 1/2hB + 1/2hb
A - 1/2hB = 1/2hb
2A - hB = hb
b = (2A-hB) / h = 2A/h - B
b = 2A/h - B
2007-01-12 09:49:45
·
answer #1
·
answered by i♥sf 5
·
1⤊
1⤋
A=1/2h(B+b)
divide by 1/2h
2A/h=B+b
subtract B
(2A/h)-B=b
2007-01-12 09:49:35
·
answer #2
·
answered by Mary Elizabeth 6
·
1⤊
1⤋
A=1/2h(B+b)
2A/h=B+b
b=2A/h-B
2007-01-12 09:54:31
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
A = 1/2h(B + b)
First: divide both sides by 1/2h...
A /(1/2h) = 1/2h(B + b) / 1/2h
A /(1/2h) = B + b
A(2)/h = B + b
2A/h = B + b
Sec: solve for "b" by isolating it on one side...subtract B from both sides...
2A/h - B = b
b = 2A/h - B
2007-01-12 09:57:02
·
answer #4
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
A = 1/2h(B + b)
All you have to do is isolate the "b" therm..
A. 2h(B+b) = 1
2.A.h.B + 2.A.h.b = 1
2.A.h.b = 1 - 2.A.h.B
b = (1 - 2.A.h.B)/(2.A.h)
2007-01-12 12:32:25
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
A = 1/2h(B + b)
2A = h(B + b)
2A/h = B + b
2A/h - B = b
b = 2A/h - B
Th
2007-01-12 11:19:02
·
answer #6
·
answered by Thermo 6
·
1⤊
0⤋
A=1/2 h(B+b) distribute 1/2 h
A=hB/2+hb/2 subtract hB/2 from each side
A-hB/2=sb/2 multiply both sided by 2/h
A/h-B=b or
b=2A/h-B
2007-01-12 10:01:34
·
answer #7
·
answered by yupchagee 7
·
1⤊
0⤋
B = (C - Ax) / y that's a reasonably basic re-association, and something you ought to have the skill to do on your guy or woman. otherwise, i wish your instructor allows you to apply Yahoo! solutions in the time of the try.
2016-10-07 01:50:44
·
answer #8
·
answered by ? 4
·
0⤊
0⤋
Multiply both sides by 2/h
2A/h = B+b
Next subtract B from each side
2A/h - B = b
2007-01-12 09:49:00
·
answer #9
·
answered by MollyMAM 6
·
2⤊
1⤋
2A/h - B = b
2007-01-12 09:49:52
·
answer #10
·
answered by Modus Operandi 6
·
1⤊
1⤋